Alcohol and parenthood: An integrative analysis of the effects of transition to parenthood in three Australasian cohorts. (1st April 2019) - Borschmann, Rohan; Becker, Denise; Spry, Elizabeth; Youssef, George J.; Olsson, Craig A.; Hutchinson, Delyse M.; Silins, Edmund; Boden, Joseph M.; Moreno-Betancur, Margarita; Najman, Jake M.; Degenhardt, Louisa; Mattick, Richard P.; et al.
Highlights: Females' alcohol consumption reduced during pregnancy and the first 12 months postpartum. Females' consumption increased as the age of their youngest child increased, up to five years of age. Little change was observed in males' drinking with the transition to parenthood. Abstract: Aims: To determine the extent to which the transition to parenthood protects against heavy and problematic alcohol consumption in young men and women. Design: Integrated participant-level data analysis from three population-based prospective Australasian cohort studies. Setting: General community; participants from the Australian Temperament Study, the Christchurch Health and Development Study, and the Victorian Adolescent Health Cohort Study. Measurements: Recent binge drinking, alcohol abuse/dependence and number of standard drinks consumed per occasion. Findings: 4015 participants (2151 females; 54%) were assessed on four occasions between ages 21 and 35. Compared to women with children aged <12 months, women who had not transitioned to parenthood were more likely to meet the criteria for alcohol abuse/dependence (fully adjusted risk ratio [RR] 3.5; 95% CI 1.5–7.9) and to report recent binge drinking (RR 3.0; 95% CI 2.1–4.3). The proportion of women meeting the criteria for alcohol abuse/dependence and/or binge drinking increased with the age of participants' youngest child, as did the mean number of standard drinks consumed on each occasion (1.8 if the youngest child was <1 year of age vs. 3.6 for 5+ years of age). Associations between parenthood and male drinking behaviour were considerably weaker. Conclusions: For most women in their twenties and thirties, parenting a child <1 year of age was associated with reduced alcohol consumption. However, this protective effect diminished after 12 months with drinking levels close to pre-parenthood levels after five years. There was little change in male drinking with the transition to parenthood.